ASSESSMENT OF BANK HEALTH LEVEL USING CAMEL METHOD AT PT BNI SYARIAH IN 2014-2018 - hanafi hanafi; sry lestari; lismawati lismawati (Institut Agama Islam Negeri Padangsidimpuan, 2022)
The background of the problem in this study is the level of bank health can be measured by looking at the financial performance of the bank. Financial performance is the result of achieving a successful financial condition of the bank in a certain period to assist investors in making investment decisions in a bank. The purpose of this study was to determine the condition of the health level of PT BNI Syariah in 2014-2018. The analytical tool used is CAMEL. The theory used in this study is a theory related to the CAMEL method. Assessment using the CAMEL method consists of CAR, PPAP, ROA, and FDR. The data used is the financial statement data obtained from the company PT Bank Negara Indonesia Syariah in 2014-2018 published through the website. This type of research is descriptive quantitative research. namely, research that emphasizes testing theories through measuring research variables with numbers and analyzing data with statistical procedures. The data source used is secondary data. The results of this study indicate that the level of bank health at PT BNI Syariah is measured by financial performance for the CAR, PPAP, ROA, and FDR ratios categorized in a healthy group.